Composite positive electrode active material and preparation method thereof, positive electrode and all-solid-state battery

By forming a LiNbO2F shell on the surface of a ternary positive electrode material or a lithium-rich manganese-based positive electrode material, the problem of easy structure damage at high voltage is solved, and the circulation performance of all-solid-state batteries and the internal resistance of the battery are significantly improved.

CN119581536AActive Publication Date: 2025-03-07SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD

Patent Information

Application Number
CN202411785597.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The structure of the ternary positive electrode material and the lithium-rich manganese-based positive electrode material are easily damaged at high voltages, resulting in a degradation of the battery's circulation performance and side-reacting with the solid electrolyte membrane, affecting the battery's performance.

Method used

A shell of fluoride LiNbO2F is formed on the surface of the ternary positive electrode material or the lithium-rich manganese-based positive electrode material. By covering the LiNbO2F shell on the surface of the core material, the high voltage stability of the positive electrode material and the contact performance with the solid electrolyte membrane are improved.

Benefits of technology

It effectively improves the high voltage stability of composite positive electrode active materials, improves the cycling performance of all-solid-state batteries, and reduces the polarization and internal resistance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581536A_ABST
    Figure CN119581536A_ABST
Patent Text Reader

Abstract

The invention relates to a composite positive electrode active material and a preparation method thereof, a positive electrode and an all-solid-state battery in the technical field of lithium battery production. The composite positive electrode active material is of a core-shell structure, the core material comprises a ternary positive electrode material or a lithium-rich manganese-based positive electrode material, and the shell layer comprises LiNbO2F. A shell layer of fluoride LiNbO2F is formed on the surface of the ternary positive electrode material or the lithium-rich manganese-based positive electrode material, so that the high-voltage stability of the composite positive electrode active material can be effectively improved, the cycle performance of the all-solid-state battery can be effectively improved, on the other hand, the solid-solid contact between the positive electrode and a solid electrolyte membrane can be effectively improved by coating LiNbO2F, and the cycle performance of the all-solid-state battery can be improved. And meanwhile, the polarization of the battery is reduced, and the internal resistance of the battery is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and more specifically to a composite positive electrode active material and a preparation method thereof, a positive electrode, and an all-solid-state battery. Background Art

[0002] With the development of all-solid-state batteries, people have higher requirements for energy density. At present, the application of ternary cathode materials and lithium-rich manganese-based cathode materials is the key to achieving high energy density of solid-state batteries. However, ternary cathode materials and lithium-rich materials often have problems of lattice oxygen release, metal dissolution, and structural collapse, which will further aggravate the side reactions with sulfide and halide electrolytes, leading to the accumulation of interface byproducts and a rapid decrease in cycle performance. Therefore, in order to further improve the interface side reactions between the cathode and the electrolyte, it is necessary to coat the cathode material. However, the current cathode material coating is mostly oxide coating, and the oxide often decomposes at high voltage, has poor high-voltage resistance, and has a poor effect on the cathode surface.

[0003] Therefore, there is an urgent need for a good coating material to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a composite positive electrode active material, a preparation method, a positive electrode and a battery.

[0005] The technical solution of the present invention is achieved in this way:

[0006] A first aspect of the present application provides a composite positive electrode active material, wherein the composite positive electrode active material is a core-shell structure, wherein the core material comprises a ternary positive electrode material or a lithium-rich manganese-based positive electrode material, and the shell layer comprises LiNbO2F.

[0007] In some embodiments, the ternary cathode material is LiNi x Co y Mn 1-x-y O2, wherein x=0.5~1.0, y>0, x+y<1.

[0008] In some embodiments, the shell layer has a thickness of 5 to 30 nm.

[0009] In some embodiments, the mass ratio of the core material to LiNbO2F is 1:(0.005-0.05).

[0010] In some embodiments, the particle size D50 of the core material is 3-12 μm.

[0011] In a second aspect, the present application provides a method for preparing the composite positive electrode active material as described above, comprising the following steps:

[0012] 1) mixing the core material, LiNbO2F and a solvent to form a mixed solution;

[0013] 2) filtering the mixed solution and drying it to obtain a precursor;

[0014] 3) Calcining the precursor to obtain a composite positive electrode active material.

[0015] In a second aspect, the present application provides a method for preparing the composite positive electrode active material as described above, comprising the following steps:

[0016] In some embodiments, the step 1) comprises: after mixing, stirring, and the stirring time is ≥ 4 hours.

[0017] In some embodiments, in step 3), the calcination temperature is 350-450° C.; and / or the calcination time is 2-4 hours.

[0018] In a third aspect, the present application provides a positive electrode, which includes the composite positive electrode active material as described in the first aspect.

[0019] In a fourth aspect, the present application provides an all-solid-state battery, comprising the composite positive electrode active material as described in the first aspect and / or the positive electrode as described in the third aspect.

[0020] Compared with the prior art, the technical solution of the present application has the following beneficial technical effects: the present application can effectively improve the high voltage stability of the composite positive electrode active material by forming a shell layer of fluoride LiNbO2F on the surface of the ternary positive electrode material or the lithium manganese-rich positive electrode material, thereby effectively improving the cycle performance of the all-solid-state battery; on the other hand, by coating LiNbO2F, the solid-solid contact between the positive electrode and the solid electrolyte membrane can be effectively improved, the interface contact between the positive electrode and the solid electrolyte membrane can be improved, and at the same time, the polarization of the battery can be reduced, thereby effectively reducing the internal resistance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM image of Example 1 of the present application.

[0022] Figure 2 dQ / dV curve diagram of Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0025] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0026] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0027] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0028] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0029] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0030] The structures of ternary positive electrode materials and lithium-rich manganese-based positive electrode materials are easily destroyed under high voltage, resulting in the degradation of the battery's cycle performance. Moreover, when used in all-solid-state batteries, they are prone to side reactions with solid electrolyte membranes containing sulfide solid electrolytes and / or halide solid electrolytes, further affecting the cycle performance of all-solid-state batteries under high voltage. In addition, in all-solid-state batteries, there is a technical problem of poor interface between the positive electrode and the solid electrolyte membrane due to solid-solid contact, resulting in a large internal resistance of the battery, which needs to be solved.

[0031] In order to solve the above problem, the present invention proposes a technical solution.

[0032] The first aspect of the present application provides a composite positive electrode active material. The composite positive electrode active material is a core-shell structure. The core material includes a ternary positive electrode material or a lithium-rich manganese-based positive electrode material, and the shell layer includes LiNbO2F.

[0033] The present application forms a fluoride LiNbO2F shell layer on the surface of the ternary positive electrode material or the lithium-manganese-rich positive electrode material, which can effectively improve the high voltage stability of the composite positive electrode active material, thereby effectively improving the cycle performance of the all-solid-state battery. On the other hand, by coating LiNbO2F, the solid-solid contact between the positive electrode and the solid electrolyte membrane can be effectively improved, the interface contact between the positive electrode and the solid electrolyte membrane can be improved, and the polarization of the battery can be reduced, thereby effectively reducing the internal resistance of the battery.

[0034] In some embodiments, the ternary cathode material is LiNi x Co y Mn 1-x-y O2, wherein x = 0.5-1.0, y> 0, x+y< 1. This setting is beneficial to improving the energy density of the battery.

[0035] In some embodiments, the lithium-rich manganese-based positive electrode material is Li a Ni b Mn c O2, where a>1, b+c=1.

[0036] In some embodiments, the shell layer has a thickness of 5 to 30 nm. It is understood that if the shell layer is too thin, coating failure may occur during the charge-discharge cycle, and if the shell layer is too thick, the release and migration of lithium ions from the positive electrode active material may be affected.

[0037] Specifically, the thickness of the shell layer can be 5 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 20 nm, 25 nm, or 30 nm. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.

[0038] In some embodiments, the mass ratio of the core material to LiNbO2F is 1:(0.005-0.05). Specifically, the mass ratio of the positive electrode active material to LiNbO2F can be 1:0.005, 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045, 1:0.05. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.

[0039] In some embodiments, the particle size D50 of the core material is 3-12 μm.

[0040] Specifically, it can be 3 μm, 4.5 μm, 5 μm, 6.2 μm, 7 μm, 8.6 μm, 9 μm, 10 μm, 11 μm, 12 μm. Of course, it can also be any value within this range, and the present invention does not impose any limitation on this.

[0041] In a second aspect, the present application provides a method for preparing the composite positive electrode active material as above, comprising the following steps:

[0042] 1) mixing the core material, LiNbO2F and a solvent to form a mixed solution;

[0043] 2) filtering the mixed solution and drying it to obtain a precursor;

[0044] 3) Calcine the precursor to obtain a positive electrode active material.

[0045] In a second aspect, the present application provides a method for preparing the composite positive electrode active material as above, comprising the following steps:

[0046] In some embodiments, step 1) comprises: after mixing, stirring, and the stirring time is ≥4h.

[0047] In some preferred embodiments, the stirring time is 4 to 20 hours.

[0048] In some preferred embodiments, the stirring speed is 300-800 rpm.

[0049] In some preferred embodiments, in step 1), the solvent is anhydrous ethanol.

[0050] In some preferred embodiments, in step 1), mixing comprises mixing at a constant temperature of 20-50°C.

[0051] In some embodiments, in step 3), the calcination temperature is 350-450°C.

[0052] In some embodiments, in step 3), the calcination time is 2 to 4 hours.

[0053] In some embodiments, in step 3), the calcination atmosphere is argon.

[0054] In some embodiments, step 1) further includes the preparation of LiNbO2F, comprising the following steps:

[0055] ① Mix Li2O, Nb2O5 and LiF powders in a molar ratio of 0.51:1:1 to form a mixture;

[0056] ② calcining the mixture, and then slowly cooling it to room temperature to obtain a calcined product;

[0057] ③ The calcined product is crushed and sieved to obtain LiNbO2F.

[0058] As one implementation mode, in step ①, the mixing method is ball milling, and the ball milling speed is 250 to 500 rpm.

[0059] As one implementation mode, in step ①, the mixing time is 4 to 8 hours.

[0060] As one embodiment, in step ②, the calcination temperature is 800-900°C.

[0061] As one implementation mode, in step ②, the calcination time is 5 to 12 hours.

[0062] As one implementation mode, in step ②, the calcination atmosphere is a mixed atmosphere of Ar and H2.

[0063] As a preferred implementation manner, in step ②, the volume proportion of H2 in the calcination atmosphere is 3% to 10%.

[0064] As one implementation mode, in step ③, the specific step of crushing is to place the calcined product into a high-energy ball mill for crushing.

[0065] As one implementation mode, in step ③, the rotation speed of the high energy ball mill is 100 to 200 rpm.

[0066] As one implementation mode, in step ③, the crushing time is 2 to 5 hours.

[0067] In a third aspect, the present application provides a positive electrode, which includes the composite positive electrode active material as described in the first aspect.

[0068] In some embodiments, the positive electrode includes a positive electrode material layer, and the positive electrode material layer includes the composite positive electrode active material disclosed in the first aspect of the present invention.

[0069] In some embodiments, the positive electrode material layer further includes a binder, which improves the bonding between the composite positive electrode active material particles and also improves the bonding between the positive electrode material layer and the positive electrode current collector.

[0070] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0071] In some embodiments, the cathode material layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0072] In some embodiments, the positive electrode sheet includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.

[0073] In some embodiments, based on the total mass of the positive electrode material layer, the mass percentage of the composite positive electrode active material particles in the positive electrode material layer is 70%-97%.

[0074] In some embodiments, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode material layer.

[0075] In some embodiments, the mass of the binder accounts for 1%-20% of the mass of the positive electrode material layer.

[0076] In some embodiments, the positive electrode plate provided by the present invention further includes solid electrolyte powder for improving the ionic conductivity of the composite positive electrode. The present invention does not limit the type of solid electrolyte powder, which may be oxide solid electrolyte powder, sulfide solid electrolyte powder, or halide solid electrolyte powder. Optionally, the mass of the solid electrolyte powder accounts for 1%-30% of the mass of the positive electrode plate; preferably 5%-20%.

[0077] In some embodiments, the thickness of the positive electrode material layer in the positive electrode plate provided by the present invention is 30-400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50-110 μm.

[0078] In a fourth aspect, the present application provides an all-solid-state battery, comprising the composite positive electrode active material as in the first aspect and / or the positive electrode as in the third aspect.

[0079] The all-solid-state battery also includes a negative electrode, which includes a negative electrode plate.

[0080] Negative electrode:

[0081] In some embodiments, the negative electrode sheet includes a current collector and a negative active material layer disposed on the current collector.

[0082] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy, Ag-C alloy or more. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0083] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.

[0084] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.

[0085] In some embodiments, the negative electrode material layer may include a binder; the binder improves the bonding between negative electrode active material particles and the bonding between the negative electrode active material and the current collector.

[0086] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.

[0087] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.

[0088] In some embodiments, the aforementioned viscosity enhancer may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.

[0089] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.

[0090] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.

[0091] In some embodiments, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0092] All-solid-state batteries also include a solid electrolyte membrane.

[0093] The solid electrolyte membrane includes a solid electrolyte.

[0094] In some embodiments, the solid electrolyte is a sulfide solid electrolyte, and the sulfide solid electrolyte includes Li2S-P2S5, Li2S-P2S5-MSx (wherein M is Si, Ge and Sn and 0≤x≤2), Li3.4Si0.4P0.6S4, Li10GeP2S11.7O0.3, Li9.6P3S12, Li7P3S11, Li9P3S9O3, Li10.35Si1.3 5P1.65S12、Li9.81Sn0.81P2.19S12、Li10(Si0.5Ge0.5)P2S12、Li(Ge0.5Sn0.5)P2S12、Li(Si0.5Sn0.5)PsS12、Li10GeP2S12(LGPS)、Li6PS5X(where X is Cl, Br or I)、Li7P2S8I、Li10.35Ge1.35P1.65 S12, Li3.25Ge0.25P0.75S4, Li10SnP2S12, Li10SiP2S12 or Li9.54Si1.74P1.44S11.7Cl0.3, or a combination of at least two thereof; typical but non-limiting combinations include combinations of Li2S-P2S5 and Li2S-P2S5-MSx (wherein M is Si, Ge and Sn and 0≤x≤2), Li3.4Si0.4 The combination of P0.6S4 and Li10GeP2S11.7O0.3, the combination of Li7P3S11, Li9P3S9O3 and Li10.35Si1.35P1.65S12, or the combination of Li9.81Sn0.81P2.19S12, Li10(Si0.5Ge0.5)P2S12, Li(Ge0.5Sn0.5)P2S12 and Li(Si0.5Sn0.5)PsS12.

[0095] In some embodiments, the solid electrolyte is a halide solid electrolyte, and the general formula of the halide solid electrolyte is Li x MX y N z , wherein 1≤x≤4, 4≤y+nz≤8, and n is the absolute value of the valence of N. The metal element M includes at least one of V, Cr, Mn, Zn, Cd, Fe, Pb, In, Y, Al, Sc, La, Lu, Ga, Zr, or Hf. X includes at least one of the halogen elements F, Cl, Br, and I. N is at least one of the non-metallic elements O and S. Exemplarily, the halide solid electrolyte includes Li3InBr 6-m Cl m (0≤m≤6), LiInX4, Li3YX6, Li3ErX6, Li3ScX6, Li3LaX6, Li 3-m Er 1-m Zr m Cl6(x≤0.6), Li 3-m Y 1-m Zr m Cl6(m≤0.6), Li3Y 1-m In m Cl6(0 <m<1)、Li2ZrX6、Li2ZrX y Oz(0<z≤1,y+z=6)、Li2ZrX y A mixture of one or more of Sz (0<z≤1, y+z=6).

[0096] In some preferred embodiments, the halide solid electrolyte includes Li2ZrCl6, Li2ZrCl5F, Li2ZrCl 5.5 O 0.25 、Li3InCl6、Li3YCl6、Li2H f Cl6、LiInBr 4、 At least one of Li3InBr6, Li3LaI6, Li3LuCl6.

[0097] The solid electrolyte includes at least one of a sulfide solid electrolyte and a halide solid electrolyte, and in addition, may also include an oxide solid electrolyte.

[0098] In some embodiments, the oxide solid electrolyte includes any one of garnet ceramics, LISICON-type oxides, NASICON-type oxides, or perovskite-type ceramics, or a combination of at least two of them. Typical but non-limiting combinations include a combination of garnet ceramics and LISICON-type oxides, a combination of LISICON-type oxides and NASICON-type oxides, or a combination of LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics.

[0099] In some embodiments, the garnet ceramic includes Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 or Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 Any one or a combination of at least two of the following, typical but non-limiting combinations include Li 6.5 Ln3Z 1.75 Te 0.25 O 12 With Li7La3Zr2O 12 The combination of Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 A combination with Li6.25Al0.25La3Zr2O12, or a combination of Li6.25Al0.25La3Zr2O12, Li6.75La3Zr1.75Nb0.25O12 and Li6.75La3Zr1.75Nb0.25O12.

[0100] In some embodiments, the LISICON-type oxide includes any one or a combination of at least two of Li14Zn(GeO4)4, Li3+x(P1-xSix)O4 (where 0 < x < 1), or Li3+xGexV1-xO4 (where 0 < x < 1). Typical but non-limiting combinations include the combination of Li14Zn(GeO4)4 and Li3+x(P1-xSix)O4 (where 0 < x < 1), the combination of Li3+x(P1-xSix)O4 (where 0 < x < 1) and Li3+xGexV1-xO4 (where 0 < x < 1), or the combination of Li14Zn(GeO4)4, Li3+x(P1-xSix)O4 (where 0 < x < 1), and Li3+xGexV1-xO4 (where 0 < x < 1).

[0101] In some embodiments, the NASICON-type oxide can be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variants, the NASICON-type oxide can be selected from any one or a combination of at least two of Li1+xAlxGe2-x(PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li1+xAlxTi2-x(PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li1+xYxZr2-x(PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li1.3Al0.3Ti1.7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3. Typical but non-limiting combinations include the combination of LAGP and LATP, the combination of LYZP and Li1.3Al0.3Ti1.7(PO4)3, or the combination of LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, and LiHf2(PO4)3.

[0102] In some embodiments, the perovskite-type ceramic includes any one or a combination of at least two of Li3.3La0.53TiO3, LiSr1.65Zr1.3Ta1.7O9, Li2x-ySr1-xTayZr1-yO3 (where x = 0.75y and 0.60 < y < 0.75), Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3, Li3xLa(2 / 3-x)TiO3 (where 0 < x < 0.25). Typical but non-limiting combinations include the combination of Li3.3La0.53TiO3 and LiSr1.65Zr1.3Ta1.7O9, the combination of Li2x-ySr1-xTayZr1-yO3 (where x = 0.75y and 0.60 < y < 0.75) and Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3, or the combination of Li3.3La0.53TiO3, LiSr1.65Zr1.3Ta1.7O9 and Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3.

[0103] The preparation method of the present invention will be described below according to the technical content of the present invention, but should not be limited to the following examples:

[0104] Example 1:

[0105] Preparation of composite cathode active material:

[0106] I. Preparation of LiNbO2F

[0107] Weigh Li2O (purity 99.9%), Nb2O5 (purity 99%), and LiF (purity 99.9%) powders according to a molar ratio of 0.51:1:1 and mix them in a planetary ball mill at a mixing speed of 300 rpm for 5 h. Subsequently, the mixture is calcined in a crucible under an Ar / H2 (5% H2) mixed atmosphere at 850 °C for 8 h, and then slowly cooled to room temperature;

[0108] The calcined LiNbO2F powder is crushed by a high-energy ball mill at 150 rpm for 3 h, and finally sieved to obtain LiNbO2F nanoparticles with uniform particle size;

[0109] II: Preparation of core material

[0110] Mix the Ni 0.9 Co 0.05 Mn 0.05 (OH)2 precursor and the lithium source LiOH in a high-speed mixer according to a molar ratio of 1:1.03. Subsequently, keep it at 450 °C for 5 h, heat it up to 725 °C at a heating rate of 3 °C / min, and calcine it in air at 725 °C for 8 h to obtain the ternary cathode material LiNi 0.9 Co 0.05 Mn0.05 O2, after sieving and iron removal, a ternary positive electrode material with a particle size of D50 = 10 μm is obtained;

[0111] 3. Preparation of composite positive electrode active materials

[0112] The obtained LiNi 0.9 Co 0.05 Mn 0.05 O2 and LiNbO2F were dissolved in anhydrous ethanol solution at a mass ratio of 1:0.02, stirred at a constant temperature of 30°C and a stirring speed of 500 rpm for 5 h in a glove box, and finally filtered and dried to obtain a precursor, which was calcined at 400°C in an argon atmosphere for 3 h to obtain a composite positive electrode active material;

[0113] The thickness of the shell is 10 nm.

[0114] Embodiment 2:

[0115] The difference between Example 2 and Example 1 is that LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2 and LiNbO2F is 1:0.03, and the other technical features are the same.

[0116] The thickness of the shell is 17 nm.

[0117] Embodiment 3:

[0118] The difference between Example 3 and Example 1 is that LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2 and LiNbO2F is 1:0.05, and the other technical features are the same.

[0119] The thickness of the shell is 30 nm.

[0120] Embodiment 4:

[0121] The difference between Example 4 and Example 1 is that LiNi 0.9 Co 0.05 Mn 0.05 The mass ratio of O2 and LiNbO2F is 1:0.005, and the other technical features are the same.

[0122] The thickness of the shell is 6 nm.

[0123] Embodiment 5:

[0124] The difference between Example 5 and Example 1 is that LiNi 0.9 Co 0.05 Mn 0.05The mass ratio of O2 and LiNbO2F is 1:0.08, and the other technical features are the same.

[0125] The thickness of the shell is 55 nm.

[0126] Embodiment 6:

[0127] The difference between Example 6 and Example 1 is that the core material in Example 3 is a lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.25 Mn 0.75 O2;

[0128] The thickness of the shell is 12 nm.

[0129] Comparative Example 1

[0130] The difference between Comparative Example 1 and Example 1 is that the composite positive electrode active material only includes the core material LiNi 0.9 Co 0.05 Mn 0.05 O2, excluding shell.

[0131] Comparative Example 2

[0132] The difference between Comparative Example 2 and Example 6 is that the composite positive electrode active material only includes the core material Li 1.2 Ni 0.25 Mn 0.75 O2, excluding shell.

[0133] Examples 1 to 6 and Comparative Examples 1 to 2 also include preparing a battery.

[0134] 1. Preparation of positive electrode

[0135] ① Preparation of positive electrode: the composite positive electrode active material, PTFE, super-P, and sulfide solid electrolyte Li6PS5Cl are mixed uniformly according to a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, and the first mixed material is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0136] ② Preparation of negative electrode: Ag-C alloy is used for negative electrode;

[0137] ③ Preparation of solid electrolyte membrane: The sulfide solid electrolyte Li6PS5Cl and the binder PTFE are mixed in a mass ratio of 65:35 and then pressed into a membrane;

[0138] ④Battery structure preparation

[0139] The positive electrode current collector, positive electrode layer, solid electrolyte membrane and negative electrode layer are stacked and hot pressed to obtain a battery structure.

[0140] Performance Test:

[0141] 1. Cycle capacity retention rate:

[0142] At a temperature of 45°C, charge at a current of 0.3C to a charging cut-off voltage of 4.25V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, discharge at a current of 0.3C to a cut-off voltage of 2.5V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 250 charge and discharge cycles.

[0143] 2. Shell thickness test

[0144] The shell thickness was mainly observed by TEM, and the average thickness was calculated at ten locations.

[0145] 3. Battery internal resistance test

[0146] At an ambient temperature of 30° C., the internal resistance of the all-solid-state batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 2 was measured using a voltage internal resistance meter.

[0147] 4. dQ / dV curve

[0148] The all-solid-state batteries prepared in Examples 1 to 5 and Comparative Example 1 were subjected to electrochemical testing at a voltage range of 2.5 V to 4.25 V. The voltage and capacity data were obtained and the dQ / dV curve was plotted. The difference between the highest peak and the lowest peak at a voltage of 4.2 V was recorded as the redox peak difference.

[0149] The technical effects of the above embodiments are compared in the following table:

[0150]

[0151] By comparing Examples 1 to 5 with Comparative Example 1, and Example 6 with Comparative Example 2, it can be seen that the present application can effectively improve the high voltage stability of the positive electrode active material by forming a shell layer of fluoride LiNbO2F on the surface of the ternary positive electrode material or the lithium-manganese-rich positive electrode material, thereby effectively improving the cycle performance of the all-solid-state battery. On the other hand, by coating LiNbO2F, the solid-solid contact between the positive electrode and the solid electrolyte membrane can be effectively improved, the interface contact between the positive electrode and the solid electrolyte membrane can be improved, and at the same time, the polarization of the battery can be reduced, thereby effectively reducing the internal resistance of the battery.

[0152] Although the present invention has described its technical scheme and embodiments in detail, for lithium-ion battery manufacturers and technicians in the same field, they can be inspired by it and select or change the technical features to replace them to obtain a technical scheme that is essentially the same as the present invention. The lithium batteries manufactured thereby should fall within the scope of protection of the present invention.

Claims

1. A composite positive electrode active material, characterized in that: The composite positive electrode active material is a core-shell structure, the core material comprises a ternary positive electrode material or a lithium-rich manganese-based positive electrode material, and the shell layer comprises LiNbO2F.

2. The composite positive electrode active material according to claim 1, characterized in that The ternary positive electrode material is LiNi x Co y Mn 1-x-y O2, wherein x=0.5~1.0, y>0, x+y<1.

3. The composite positive electrode active material according to claim 1, characterized in that: The thickness of the shell layer is 5nm to 30nm.

4. The composite positive electrode active material according to claim 1, characterized in that: The mass ratio of the core material to LiNbO2F is 1:(0.005-0.05).

5. The composite positive electrode active material according to claim 1, characterized in that: The particle size D50 of the core material is 3 to 12 μm.

6. A method for preparing the composite positive electrode active material according to claim 1, characterized in that: The steps include: 1) mixing the core material, LiNbO2F and a solvent to form a mixed solution; 2) filtering the mixed solution and drying it to obtain a precursor; 3) Calcining the precursor to obtain a composite positive electrode active material.

7. The preparation method according to claim 6, characterized in that: The step 1) comprises: stirring after mixing, and the stirring time is ≥4h.

8. The preparation method according to claim 6, characterized in that: In the step 3), the calcination temperature is 350-450° C.; and / or the calcination time is 2-4 hours.

9. A positive electrode, characterized in that The positive electrode comprises the composite positive electrode active material as claimed in claim 1.

10. All-solid-state battery, characterized in that: The all-solid-state battery comprises the composite positive electrode active material as claimed in claim 1 and / or the positive electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Positive electrode active material and battery

    CN108336328A

  • Lithium ion battery positive pole material, preparation method thereof, lithium ion battery positive pole and all-solid-state lithium battery

    CN110660976A

  • Positive electrode active material containing lithium composite oxyfluoride and organosilicon compound, and battery including positive electrode containing the positive electrode active material

    US20180205087A1

  • Positive electrode material and battery using same

    US20200350621A1

  • LimMOxFy SHELL FORMATION ON CATHODE CERAMIC PARTICLE FOR LI ION BATTERY THROUGH ONIUM METAL OXIDE FLUORIDE PRECURSOR

    US20210367227A1

Cited By

  • All-solid-state battery, preparation method thereof and battery module

    CN121748291A